THE DAILY MUSCLE PERFORMANCE ON COOPERATION SHARIA ARIDDAH BASERAH - Yella Febriona; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The study to also provide a comprehensive health analysis of the liquditiy ratio,solvency and proficiency of the sharia cooperative ariddah baserah district of the singingin district in 2016-2020.The study Uses a secondary  data of the data the author acquirwd therough the financial reports of the ariddah sariah baserah sariah cooperation that researcher need to combine liquidity.solvabilitiy and capabilitiy ratio.Analysis shows a  saram basd financial report analysis from cooperation sariah ariddah baserah period 2014-2020 based on the liquiditiy ratio of solvabilitiy and capabilitiy is :1;analiysis ratio liquditiy qurrnet ratio got a’ not healty rap “2);anaysisi ratio solvabilitiy total asset to debt ratio unwell assessment device” and net worth to debt not healty  ”3);analysis ratio capabilitiy the  capital itself gets  a not healty judgment and return on asset not healty poor judgement”4);according to ministry of state regulations cooperation, small and medium enterprises, healt rates of trade operatives and 0xford cooperation sariah ariddah baserah goat lousy predicate. Password:Financial performance analiysis with a ratio  likuiditiy, solvabilitiy and capabilitiy.